EMPLOYEES ENVIRONMENTAL PERFORMANCE BASED ON CONSCIENTIOUSNESS, AGREEABLESNESS, NEUROTICISM, OPENNESS, AND EXTRAVERSION - Nadiroh Nadiroh; Endah Setyaningrum (Program Studi Magister Manajemen Lingkungan, 2016)
This research aims to determine the relationship between the big five personality factor (conscientiousness, agreeableness, neuroticism, openness, and extraversion) with an employee’s environmental performance on employees at Jakarta Industrial Park (EJIP) Cikarang Company. The method used is quantitative method with a correlation technique. The research was conducted from November 2016 to March 2016, with a total sample of 85 people. Analysis of Variance (ANOVA) showed association between conscientiousness, agreeableness, neuroticism, openness, and extraversion with an employee’s environmental performance, as calculated F value of 4.02 to the level of sig. of .01, where the figure is much lower than the level of sig. .05. These result indicate that conscientiousness, agreeableness, neuroticism, openness, and extraversion significantly affect the employee’s environmental performance.